Textile reinforced mortar to masonry bond under static and fatigue loading - Makashev, Kuanysh (2022)
There is a growing interest in strengthening existing masonry buildings and structures due to their continuous structural deterioration, which is accelerated by the effect of adverse environmental actions, e.g., earthquakes, high-speed winds, heavy rainfalls and the continuous increase of traffic loads. Textile Reinforced Mortars (TRM) have been proven to provide several advantages over more traditional strengthening approaches; they are applicable in low temperatures, provide fire resistance, and are low cost. TRM, that belong to the more general family of Fabric Reinforced Cementitious Matrices (FRCM) - involve high strength fibre textile materials impregnated in inorganic cement or lime-based mortars. As in every externally bonded strengthening technique, one of the key parameters controlling the effectiveness of TRM is the bond between the strengthening material and the substrate. Over the past fifteen years, the mechanics of TRM to masonry bond have been investigated experimentally, analytically, and numerically for the case of quasi-static loading. However, experiments demonstrate a large variability vis-a-vis the anticipated bond strength. Conversely, the case of fatigue loading has not garnered much attention. Experiments conducted on FRP strengthened concrete specimens have demonstrated the detrimental effect of fatigue on the corresponding interfacial properties. With the objective of further investigating the effect of bond and contribute to the state-of-the-art in interface properties, this Thesis provides results from an experimental investigation on the TRM to masonry bond strength under monotonic and cyclic loading conditions. At the first stage, the textile reinforcement tensile properties were determined by carrying out tensile tests on bare textiles. Next, the bond behaviour between TRM and masonry substrate under quasi-static loading was extensively investigated. The investigated parameters were the bond length, the textile-fibre material and the epoxy resin coating. Finally, for the first time, a series of single-lap shear tests under fatigue loading has been conducted on textile fibre TRM bonded to masonry, considering various bond lengths and load ranges. The experimental results establish that TRM and masonry bond behaviour depends on textile materials used and the anchorage lengths. Furthermore, this work highlights the beneficial effect of the epoxy-resin coating compared to the uncoated counterpart specimens; it increases the fibre textiles’ tensile properties, improves the bonding conditions, and alters the failure mode of carbon and glass fibre-textile material. The results of bond behaviour under low cycle fatigue loading tests showed that the load range considerably affects the fatigue life of TRM strengthened components resulting in significantly lower strengths when compared to the quasi-static case.